Depressive symptom trajectories and incident metabolic syndrome in middle-aged and older adults: A longitudinal analysis of the ELSA study - Chen, Xuhui; Wu, Jiaofen; Wang, Ying; He, Yulian; Ye, Honghua; Liu, Jianhui (Frontiers in Psychiatry, 2025)
BackgroundThe association between late-life depressive symptoms and metabolic syndrome (MetS) remains a critical public health concern, yet most existing evidence relies on cross-sectional designs that fail to capture the dynamic nature of depression. This longitudinal study aimed to investigate how depressive symptom trajectories influence MetS risk in middle-aged and older adults, while examining potential effect modification by sociodemographic and lifestyle factors.MethodsUsing data from the English Longitudinal Study of Ageing (ELSA), we identified three trajectories of depressive symptoms (persistent low, moderate, and high) through group-based trajectory modeling (GBTM) across four survey waves. Multivariable logistic regression assessed associations between trajectories and incident MetS, adjusted for age, sex, education, marital status, smoking, drinking, and income. Stratified analyses evaluated effect modification by these factors.ResultsParticipants with persistent moderate (OR=1.08, 95% CI: 1.03–1.15) and high (OR=1.07, 1.01–1.14) trajectories had significantly higher MetS risk versus the low trajectory. Associations were strongest in adults <65 years, married individuals, and those with smoking/drinking habits (p <0.05), but did not vary by sex. Physical activity mediated 18.9% of the total effect (95% CI: 5–37%).ConclusionDynamic depressive symptoms independently predict MetS risk, with amplified effects in younger, married, and health-risk subgroups. Targeted interventions addressing both depressive symptoms and modifiable behaviors (e.g., physical activity) may mitigate metabolic risk in aging populations.